2010
DOI: 10.4161/cbt.9.2.10283
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of a novel gene gankyrin correlates with the malignant phenotype of colorectal cancer

Abstract: Gankyrin, a small and highly conserved protein which is identical to the p28 gene product, was found to be related with the malignant phenotypes in liver and esophageal carcinoma. However, the roles of gankyrin in colorectal carcinoma (CRC) are still unknown. In the present study, the gankyrin mRNA and protein expression in human CRC cell lines and clinical tissue samples were evaluated and correlated with clinicopathological features. Possible mechanisms by which gankyrin regulates the malignant phenotype of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 25 publications
(27 reference statements)
1
45
0
Order By: Relevance
“…The expression of Gankyrin has been investigated in a variety of cancers with nearly universal findings that showed elevated protein and/or mRNA levels in cancers when compared with normal counterparts (4)(5). Gankyrin has been shown to be involved in carcinogenesis and oncogene-induced tumor onset and progression (4,(6)(7)(8)(9)(10). Overexpression of Gankyrin promotes cellular proliferation by targeting retinoblastoma protein (Rb), leading to subsequent Rb degradation, activation of E2F transcription factor, and DNA synthesis of genes required for G 1 -S-phase transition (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of Gankyrin has been investigated in a variety of cancers with nearly universal findings that showed elevated protein and/or mRNA levels in cancers when compared with normal counterparts (4)(5). Gankyrin has been shown to be involved in carcinogenesis and oncogene-induced tumor onset and progression (4,(6)(7)(8)(9)(10). Overexpression of Gankyrin promotes cellular proliferation by targeting retinoblastoma protein (Rb), leading to subsequent Rb degradation, activation of E2F transcription factor, and DNA synthesis of genes required for G 1 -S-phase transition (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Examination of gankyrin expression in colorectral carcinoma (CRC) samples showed that gankyrin is dramatically increased in majority of CRC samples [72]. It has been shown that RNAi-mediated inhibition of gankyrin in the CRC cells inhibits proliferation of these cells [72].…”
Section: Introductionmentioning
confidence: 99%
“…6 In addition, gankyrin plays an essential role in Ras-initiated tumorigenesis, which is operative in ∼30% of all cancers. 7 Protein–protein interactions (PPIs) involving gankyrin are of great interest in basic research and as therapeutic targets.…”
mentioning
confidence: 99%